B cell homeostasis is disturbed by immunosuppressive therapies in patients with ANCA-associated vasculitides. (November 2013) - Thiel, Jens; Salzer, Ulrich; Hässler, Fabian; Effelsberg, Nora M.; Hentze, Carolin; Sic, Heiko; Bartsch, Marit; Miehle, Nikolaus; Peter, Hans Hartmut; Warnatz, Klaus; Schlesier, Michael; Voll, Reinhard E.; et al.
Abstract B-lymphocytes play a pivotal role in ANCA-associated vasculitides (AAV). The homeostasis of peripheral human B-lymphocyte subpopulations is tightly regulated, but may be disturbed in autoimmune disease or following immunosuppressive therapies. To elucidate the effect of immunosuppression and the relevance of B-lymphocyte disturbances, the B-lymphocyte compartment was analysed in 61 AAV patients. After immunosuppressive treatment a general B-lymphocytopenia developed in AAV patients. Within the B-lymphocyte subpopulations transitional B cells are the first maturation stage found in the peripheral blood. Transitional B-lymphocytes were significantly lower in AAV patients after immunosuppressive therapy compared to healthy controls. Furthermore, marginal zone B cells – a B-lymphocyte population protecting against encapsulated bacteria -- were markedly lowered after immunosuppressive therapy in AAV patients. AAV patients treated with immunosuppressants had lower numbers of naïve and memory B-lymphocytes. Numbers of marginal zone B cells, memory B cells and plasmablasts correlated with concentrations of immunoglobulins. We evaluated plasmablasts for a potential correlation with disease activity. Different from what has been reported for e.g. large vessel vasculitis, absolute numbers of plasmablasts were not increased in patients with AAV and showed no correlation to disease activity. As low transitional B cells after treatment with immunosuppressants indicated an impaired early B-lymphocyte development, seven patients treated with the B cell depleting agent rituximab (RTX) because of relapsing disease activity were analysed for their B cell repopulation kinetics. In the majority of these patients repopulation of the peripheral B cell compartment by newly formed transitional B cells after RTX treatment was constricted and delayed.